2023
DOI: 10.1007/s11135-023-01670-3
|View full text |Cite
|
Sign up to set email alerts
|

Skills, availability, willingness, expected participation and burden of sharing visual data within the frame of web surveys

Abstract: Although there is literature on the willingness to share visual data in the frame of web surveys and the actual participation when asked to do so, no research has investigated the skills of the participants to create and share visual data and the availability of such data, along with the willingness to share them. Furthermore, information on the burden associated with answering conventional questions and performing visual data-related tasks is also scarce. Our paper aims to fill those gaps, considering images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Thus, we decided to limit the participation to respondents using smartphones and tablets, which allow for capturing photos more easily. This decision was supported by previous studies conducted with the same opt-in panel in Spain ( Netquest ), which have reported that smartphones are the primary device used by respondents to answer surveys ( e.g., 69% in Iglesias & Revilla, 2023 , or 64% among millennials in Bosch et al , 2019b ). In order to guarantee mobile-only participation, the survey was programmed such that if a participant tried to connect to the survey through a PC, the following message was shown: “This survey should be answered from a smartphone or tablet.…”
Section: Protocolmentioning
confidence: 58%
See 2 more Smart Citations
“…Thus, we decided to limit the participation to respondents using smartphones and tablets, which allow for capturing photos more easily. This decision was supported by previous studies conducted with the same opt-in panel in Spain ( Netquest ), which have reported that smartphones are the primary device used by respondents to answer surveys ( e.g., 69% in Iglesias & Revilla, 2023 , or 64% among millennials in Bosch et al , 2019b ). In order to guarantee mobile-only participation, the survey was programmed such that if a participant tried to connect to the survey through a PC, the following message was shown: “This survey should be answered from a smartphone or tablet.…”
Section: Protocolmentioning
confidence: 58%
“…Answer from their main residence : Iglesias and Revilla (2023) found that the most limiting factor for sending images is related to the availability of the data. In particular, when asking for photos that must be captured during the survey, they found that between 17.1% and 33.7% of the respondents are not in a situation allowing them to take such photos.…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no experimental evidence directly compares these three approaches to data donation, prior research has employed images, videos, and enhanced recall to collect data in surveys (Bosch and Revilla, 2019;Iglesias and Revilla, 2023), including data donations, with varying degrees of success. Regarding screenshots, studies have reported donation rates ranging from 9% to 41.1% (Hodes and Thomas, 2020;Ohme et al, 2021;Gower and Moreno, 2018;Rosenthal et al, 2021).…”
Section: The Challenges Of Measuring Mobile and App Usage Through Dat...mentioning
confidence: 99%